2022
DOI: 10.3389/fpsyg.2022.790211
|View full text |Cite
|
Sign up to set email alerts
|

Equal Representation Does Not Mean Equal Opportunity: Women Academics Perceive a Thicker Glass Ceiling in Social and Behavioral Fields Than in the Natural Sciences and Economics

Abstract: In the study of women in academia, the focus is often particularly on women’s stark underrepresentation in the math-intensive fields of natural sciences, technology, and economics (NTE). In the non-math-intensive of fields life, social and behavioral (LSB) sciences, gender issues are seemingly less at stake because, on average, women are well-represented. However, in the current study, we demonstrate that equal gender representation in LSB disciplines does not guarantee women’s equal opportunity to advance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 103 publications
(138 reference statements)
1
18
0
Order By: Relevance
“…This review and others (e.g., Gruber et al, 2020 ) provide evidence that examining gender disparities in the social sciences is warranted. Less national attention and federal funding have focused on gender inequities in the social sciences because many of these fields have better representation of women ( American Psychological Association [APA], 2017 ; Begeny et al, 2020 ; Gruber et al, 2020 ; Van Veelen and Derks, 2022 ). Despite higher degree attainment among women in the social sciences, psychology, anthropology, and sociology, women faculty are underrepresented at higher faculty ranks and among economics and political science faculty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review and others (e.g., Gruber et al, 2020 ) provide evidence that examining gender disparities in the social sciences is warranted. Less national attention and federal funding have focused on gender inequities in the social sciences because many of these fields have better representation of women ( American Psychological Association [APA], 2017 ; Begeny et al, 2020 ; Gruber et al, 2020 ; Van Veelen and Derks, 2022 ). Despite higher degree attainment among women in the social sciences, psychology, anthropology, and sociology, women faculty are underrepresented at higher faculty ranks and among economics and political science faculty.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural biases suggest that once women have achieved parity or are well-represented in an academic domain, gender bias no longer exists ( Begeny et al, 2020 ). This review challenges that notion by providing evidence from social science domains in which women are well-represented but continue to face systemic gender biases (see Van Veelen and Derks, 2022 ). For example, women doctoral-level social scientists average $14,000 less than men regardless of academic rank ( National Center for Science and Engineering Statistics [NCSES], 2021b ).…”
Section: Introductionmentioning
confidence: 98%
“…Taken together, these findings suggest that gender stereotypes persist even in disciplines where the overall percentage of women is high and that since gender stereotypes' existence is less obvious, they have significant psychological consequences. In line with this view, van Veelen and Derks (2022) found that in the social sciences -but not in natural sciences, technology, and economics -women assistant and associate professors perceived a thicker glass ceiling than their men colleagues and considered it less likely to become full professors the thicker they perceived the glass ceiling to be (with no such moderated mediation appearing for men).…”
Section: Introductionmentioning
confidence: 87%
“… van Veelen and Derks (2022) had their research participants estimate the likelihood that they will become a full professor during their career. Such expectations of success are an empirically well-established predictor of achievement-related choices and persistence in academia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation